COVID-19 incidence and cardiorespiratory fitness among first-year college students - Catherine E. Alvaro; Kyle S. Levers; Matthew D. Barberio; Yichen Jin; Andrew M. Stranieri; Jennifer M. Sacheck (Frontiers Media S.A., 2024)
ObjectiveWith the emergence of the COVID-19 virus, there was a widespread infection rate among college campuses, creating a need to understand the impact of COVID-19 infection on the health and wellbeing of adolescents. The aim of this study was to examine COVID-19 incidence and cardiorespiratory fitness (CRF) among undergraduate students in the 2 years post-COVID-19 pandemic lock-down.ParticipantsParticipants (n = 151) included undergraduate college freshmen students during the 2021-2022 and 2022-2023 academic years.MethodsA series of annual surveys (n = 151) and laboratory measures among a sub-sample of participants (n = 28) were conducted to assess COVID-19 incidence, CRF, anthropometrics, and physical activity (PA).ResultsOver half of participants self-reported COVID-19 infection (59%), "good" or better CRF, a healthy body mass index (BMI), and 25% met PA recommendations. Nearly a quarter, (24%) perceived a negative impact of COVID-19 on their CRF and although not statistically significant, participants who contracted COVID-19 had 46% lower odds of having a positive perception of CRF than those who did not contract COVID-19 before. However, students who were more physically active were more likely to perceive a negative impact of COVID-19 incidence on their CRF (p = 0.035).ConclusionAlthough no relationship was detected between COVID-19 and CRF, those who perceived a negative impact of COVID-19 on their CRF reported engaging in more physical activity.